Einstein-Weyl structures on lightlike hypersurfaces - ATINDOGBE, COMLAN CYRIAQUE; OGOUYANDJOU, KOLADÉ SIMPLICE EPHREM CARLOS; BERARD BERGERY, Lionel (My University, 2013)
We study Weyl structures on lightlike hypersurfaces endowed with a conformal structure of certain type and specific screen distribution: the Weyl screen structures. We investigate various differential geometric properties of Einstein–Weyl screen structures on lightlike hypersurfaces and show that, for ambient Lorentzian space R n+2 1 and a totally umbilical screen foliation, there is a strong interplay with the induced (Riemannian) Weyl-structure on the leaves.
Keywords: Lightlike hypersurface; Screen distribution; Einstein–Weyl structure